The theme of sustainability in rural areas from a scientific approach - Seidler, Eluane Parizotto; Andreatta, Tanice; Ciechowicz, Izis Freire Santos; Spanevello, Rosani Marisa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The scientific production in the area of sustainability can be considered broad and based on discussions that portray the concern with this theme. With that aimed to analyze the state of the art related to the theme of sustainability in rural areas, besides the emergence of tools and/or methods for performing measurement. The research method used was a bibliometric study from a quantitative approach, and is considered the scientific literature published between 2008 and 2017. Thus, a search on the Scopus database was conducted from 2008 to 2017. In a broader perspective, considering the analyzed period, growth was identified in scientific production focused on the theme of sustainability in rural areas, especially from 2014. More specifically, as regards the assessment tools and/or methods to measure the levels of rural sustainability, it can be said that a set of them is available for use in different contexts. The most cited articles in this topic discuss the objectives, form of operationalization, potentialities and limitations of these tools and/or methods. Although they are presented as innovative and greatly expanded applicability, some authors emphasize the importance of carrying out adaptations to meet local and/or regional specificities.